State Succession in Regard to State Responsibility: Succession to Obligations Where the Predecessor State Ceases to Exist - Reyes Gajardo, Ignacio (Revista Tribuna Internacional, 2021)
The present work addresses the topic of State succession in regard to State responsibility. This paper will focus on the question of whether, under international law, the possibility of succession to the obligations arising from the international responsibility of a predecessor State is feasible when this liable predecessor State ceases to exist. The importance of this topic has led the International Law Commission to include it in its programme of work carried during its sixty-ninth session, whereby the Commission has prepared draft articles and adopted a position that will also be critically analysed. In doing so, this paper incurs into a relevant review of part of the scarce and diverse state practice on this matter as well as relevant literature and legal instruments. Furthermore, the ILC, the Institute of International Law and part of the doctrine have proposed exceptions to the traditional general rule of non-succession. It has been argued, however, that these do not in themselves constitute exceptions to non-succession, but rather solutions given by international law found in areas different than that of State succession. Therefore, an examination of these ‘departures’ of the general rule will take place to be able to determine their nature.